PENGARUH TINGKAT KEKAYAAN, TINGKAT KETERGANTUNGAN DAERAH, LEVERAGE, DAN TEMUAN AUDIT BPK TERHADAP KINERJA KEUANGAN DAERAH DI INDONESIA - Alamanda Marcsha, (2022)
This study aims to determine the effect of wealth level, intergovernmental revenue, leverage, and BPK audit findings on the financial performance of local governments in Sumatra Island in 2017-2019. This research is a type of quantitative research that uses secondary data in the form of Examination Results Reports on Regional Government Financial Reports. This study used a sample of 154 districts/cities located on the island of Sumatra. The technique for analyzing the data in this study uses a regression model selection test, classical assumption test, multiple linear regression, and partial hypothesis testing (t test) using the STATA version 16 tool with significant level of 0.05%. Based on the results of data analysis, it can be concluded that intergovernmental revenue and leverage have positive significant effect on local government financial performance. While wealth level and BPK audit findings have no effect on local government financial performance.